Multianalytical Characterization of Byzantine Wall Paintings by SEM-EDX, μ-XRD, Raman and FTIR Techniques - Şimşek, Onur; Özbaş, Fatih; Kaygısız, Ersin; Yasayan, Gözem; ILDIZ, GÜLCE ÖĞRÜÇ (TÜBİTAK, 2025)
In this study, various analytical methods were employed to examine the mineral based natural pigments in the frescoes of the medieval (9(th) century) Byzantine church, known today as the Atik Mustafa Pasha Mosque. The techniques include mu -X-ray diffraction (mu -XRD), Raman and Fourier transform infrared (FTIR) spectroscopies, and scanning electron microscopy coupled with energy dispersive X-ray spectroscopy (SEM-EDX). The SEM-EDX technique enabled the identification of the chemical element composition in the studied pieces, while Raman and FTIR spectroscopies, as well as XRD, allowed the identification of mineral phases and mineral based natural pigments in the paints of the frescoes. Fragments of various colors (red, black, yellow, green, pink, cream, and white) were investigated. The analyses showed that the red (and pink) tones were primarily due to hematite (Fe2O3), goethite (FeO(OH) and cinnabar (HgS), amorphous carbon (C) was used to achieve the black color. Yellow tones were mostly attributed to limonite (FeO(OH)nH(2)O) and the greens were the result of celadonite (K(Mg,Fe2+)(Fe3+,Al)[Si4O10](OH)(2)), while the white color was provided by calcite. The combined application of the different analytical methods used proved to be a powerful tool for identifying and determining the compositional makeup of the mineral based natural pigments present in the studied samples. This highlights the importance of a multi-analytical approach in characterizing the investigated historical wall paintings.
Keywords: Byzantine Wall Paintings; Cultural Heritage; FTIR; Mineral Based Natural Pigments; Raman; µ-XRD